Controle social: a não arrecadação de contribuição de melhoria no município de Santa Maria, RS - Silva, Tanise Parmeggiani da (2021)
Municipalities need revenues to carry out policies and public works, in order to ensure the social well-being of citizens. Thus, this study aims to explain the reason for the lack of collection of the contribution for improvement by the Municipality of Santa Maria (RS) in the period from 2016 to 2020. To achieve the objectives, the chosen research strategy was the case study, in a qualitative and exploratory character, having as theoretical basis the Theory of Public Choice and Decision Theory. The Public Choice and Decision Theories were used to balance the manager's deliberation against the waiver of revenue, which in this context the lack (or scarcity) of investigations by external control bodies and the lack of accountability on the matter could also contribute to the decision of not charging is verified in the Municipality of Santa Maria (RS). Information was collected through multiple sources of evidence such as documents and legislation, electronic databases, e-mails to agencies and entities, as well as direct observation. The search for municipal documents by electronic means was prioritized to verify the releases of municipal revenues and information about the work carried out, in addition to the legislation governing the matter at the municipal level, in view of the bias of the study through social control. After the organization and processing of the information, the findings were submitted to content analysis, as well as the triangulation of the collected data and the correlation with the theories that were the object of research. The main results found were that the Municipality of Santa Maria (RS) does not collect improvement contribution values due to a decision of the municipal manager, even though this is on the list of municipal taxes and there are works subject to taxation, with public improvements that contribute for the valuation of real estate. In addition, there is no analysis of external control over the specific tax. The main conclusions are that the collection of the tax is no longer carried out by the manager due to insufficiency in the administrative structure (such as the lack of public servants), due to a legal deficiency (legislation pending improvement) and procedural (clearer procedures regarding to real estate valuation). Still, the collection is not carried out due to the lack of investigations by external control bodies, a situation that gives the manager confidence in his impunity in relation to the waiver of revenues.